Effects of cover crops on soil structure and on yield of subsequent arable crops grown under strip tillage on an eroded alfisol. - Wilson, G.F.; Lal, R.; Okigbo, B. (1982)
Effects of weed fallow and of three grasses and five leguminous cover crops were investigated on soil structure of an eroded Alfisol. Crop growth and yields of subsequently grown arable crops were assessed under strip-tillage through the mechanically or chemically suppressed sods. Cover crops and fallowing improved soil organic matter content, total N, water retention and transmission properties, and decreased bulk density only in the top 0–10 cm depth. The improvements rendered were, however, slight. Grasses were difficult to suppress with paraquat or mechanical mowing, which resulted in low or negligible yield of maize, cowpea, and cassava. Leguminous covers were easily suppressed with paraquat application, and resulted in good yield of maize and cowpea. Mechanical mowing was as successful as herbicide application for suppressing Stylosanthes guianensis and resulted in satisfactory yield of maize and cowpea. Yield of cassava tubers was extremely low due to shallow surface soil, compacted sub-soil horizons, and competition from weeds and regrown cover crops. Results are discussed in terms of the amelioration of eroded and degraded soil.